Prinsip keluarga Islam mendepani norma baharu semasa pandemik covid-19 Islamic family principles in facing the new norms during the covid-19 pandemic - Mochammad Sahid, Mualimin; Hashim, Hasnizam; Fettane, Amar (Fakulti Syariah dan Undang-Undang USIM, 2020)
The Covid-19 pandemic that hits almost every corner of the world has affected the structure of human physical life that was the victim of the Corana virus infection. The current pandemic has also changed the order of society, especially at the smallest level, namely the family. As the most important part of society, the family is a source of strength to develop the nation and country as well as establishment of a civilization. Islam as a guide and way of life has universal noble values. It is also a key reference in forming a strong family and able to face all current challenges. The success and strength of a nation and country depends on the strength of a society and family institution. this article aims to explain the important aspects that support the strength of the post-pandemic covid-19 family and Islamic guidance in the concept of family in facing new normal challenges. Based on the facts and information gathered from various sources and literature especially writings about the covid-19 pandemic, new norms and the concept of family in Islam, this article obtains some research results, among them is that there are many lessons learned from the disaster of the covid-19 pandemic which puts people in a test and makes them stronger if they face all challenges with continuous efforts and positive attitudes. The concept of the Islamic family which are based on the teachings of the Qur’an and the Sunnah, if applied correctly, it will produce a strong family structure. In addition, the new norms as the current practices and habits in general have been contained within the values of Islamic teachings that are not realized and have not been perfectly practiced by society. Therefore, it is important to return to the complete teachings of Islam in order to understand the concept of the family and strengthen this institution while facing the new normal during the Covid-19 pandemic.